UMP, Dapur Infaq collaborate on digital infrastructure development for community benefit - Mimi Rabita, Abdul Wahit (2021)
KUANTAN, 6 April 2021 - Universiti Malaysia Pahang (UMP) and Pertubuhan Dapur Infaq Ummah Kuantan (Dapur Infaq) for the first time collaborated in the development of a digital application that will benefit the local community.